“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Zn–VI quasiparticle gaps and optical spectra from many-body calculations - Riefer, Arthur; Weber, Nils; Mund, Johannes; Yakovlev, Dmitri R.; Bayer, Manfred; Schindlmayr, Arno; Meier, Cedrik; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
The electronic band structures of hexagonal ZnO and cubic ZnS, ZnSe, and ZnTe compounds are determined within hybrid-density-functional theory and quasiparticle calculations. It is found that the band-edge energies calculated on the G0W0 (Zn chalcogenides) or GW (ZnO) level of theory agree well with experiment, while fully self-consistent QSGW calculations are required for the correct description of the Zn 3d bands. The quasiparticle band structures are used to calculate the linear response and second-harmonic-generation (SHG) spectra of the Zn–VI compounds. Excitonic effects in the optical absorption are accounted for within the Bethe–Salpeter approach. The calculated spectra are discussed in the context of previous experimental data and present SHG measurements for ZnO.

LiNbO3 surfaces from a microscopic perspective - Sanna, Simone; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Advanced capabilities for materials modelling with Quantum ESPRESSO - Giannozzi, P; Andreussi, O; Brumme, T; Bunau, O; Buongiorno Nardelli, M; Calandra, M; Car, R; Cavazzoni, C; Ceresoli, D; Cococcioni, M; Colonna, N; Carnimeo, I; et al. (Journal of Physics: Condensed Matter)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Phonon dispersion and zero-point renormalization of LiNbO3 from density-functional perturbation theory - Friedrich, Michael; Riefer, Arthur; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
The vibrational properties of stoichiometric LiNbO3 are analyzed within density-functional perturbation theory in order to obtain the complete phonon dispersion of the material. The phonon density of states of the ferroelectric (paraelectric) phase shows two (one) distinct band gaps separating the high-frequency (~800 cm−1) optical branches from the continuum of acoustic and lower optical phonon states. This result leads to specific heat capacites in close agreement with experimental measurements in the range 0–350 K and a Debye temperature of 574 K. The calculated zero-point renormalization of the electronic Kohn–Sham eigenvalues reveals a strong dependence on the phonon wave vectors, especially near Γ. Integrated over all phonon modes, our results indicate a vibrational correction of the electronic band gap of 0.41 eV at 0 K, which is in excellent agreement with the extrapolated temperature-dependent measurements.

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)
The Kane–Mele model was previously used to describe effective spin–orbit couplings (SOCs) in graphene. Here we extend this model and also incorporate curvature effects to analyze the combined influence of SOC and curvature on the band structure of carbon nanotubes (CNTs). The extended model then reproduces the chirality-dependent asymmetric electron-hole splitting for semiconducting CNTs and in the band structure for metallic CNTs shows an opening of the band gap and a change of the Fermi wave vector with spin. For chiral semiconducting CNTs with large chiral angle we show that the spin-splitting configuration of bands near the Fermi energy depends on the value of $\text{mod}(2n+m,3)$ .

The atomic structure of ternary amorphous TixSi1−xO2hybrid oxides - Landmann, M; Köhler, T; Rauls, E; Frauenheim, T; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

The effect of (NH4)2Sxpassivation on the (311)A GaAs surface and its use in AlGaAs/GaAs heterostructure devices - Carrad, D J; Burke, A M; Reece, P J; Lyttleton, R W; Waddington, D E J; Rai, A; Reuter, Dirk; Wieck, A D; Micolich, A P (Journal of Physics: Condensed Matter)

Elemental distribution, solute solubility and defect free volume in nanocrystalline restricted-equilibrium Cu–Ag alloys - Riedl, Thomas; Kirchner, A; Eymann, K; Shariq, A; Schlesiger, R; Schmitz, G; Ruhnow, M; Kieback, B (Journal of Physics: Condensed Matter)
In this article we study the elemental distribution and solute solubility in nanocrystalline alloys of immiscible components near restricted equilibrium for the case of the binary Cu–Ag system. As predicted from thermodynamic considerations, a grain boundary segregated monophase alloy is observed in the annealed mechanically alloyed state for low Ag content by using atom probe tomography. From the detected Ag solute grain boundary enrichment the segregation free enthalpy is estimated to range between -25 and -49 kJ mol^-1 following the McLean equation, in agreement with values reported for coarse-grained Cu–Ag. The extension of the alloying range is described by a two-domain thermodynamic model that considers the excess free volume in the grain boundaries and the strain in the strain interior on the basis of the universal equation of state at negative pressure. To access the grain boundary volumetric strain experimentally, a method based on a combination of density measurements and microscopical quantification of closed pore areas is presented. Moreover, we apply x-ray diffraction line broadening analysis to determine the local strain amplitude, which yields a root-mean-square microstrain of 0.3% for a grain size of 30 nm. It is shown that the grain boundary free volume represents the major origin for the global solubility enhancement in nanocrystalline Cu–Ag at 503 K.

Hybrid functionals and GW approximation in the FLAPW method - Friedrich, Christoph; Betzinger, Markus; Schlipf, Martin; Blügel, Stefan; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
We present recent advances in numerical implementations of hybrid functionals and the GW approximation within the full-potential linearized augmented-plane-wave (FLAPW) method. The former is an approximation for the exchange–correlation contribution to the total energy functional in density-functional theory, and the latter is an approximation for the electronic self-energy in the framework of many-body perturbation theory. All implementations employ the mixed product basis, which has evolved into a versatile basis for the products of wave functions, describing the incoming and outgoing states of an electron that is scattered by interacting with another electron. It can thus be used for representing the nonlocal potential in hybrid functionals as well as the screened interaction and related quantities in GW calculations. In particular, the six-dimensional space integrals of the Hamiltonian exchange matrix elements (and exchange self-energy) decompose into sums over vector–matrix–vector products, which can be evaluated easily. The correlation part of the GW self-energy, which contains a time or frequency dependence, is calculated on the imaginary frequency axis with a subsequent analytic continuation to the real axis or, alternatively, by a direct frequency convolution of the Green function G and the dynamically screened Coulomb interaction W along a contour integration path that avoids the poles of the Green function. Hybrid-functional and GW calculations are notoriously computationally expensive. We present a number of tricks that reduce the computational cost considerably, including the use of spatial and time-reversal symmetries, modifications of the mixed product basis with the aim to optimize it for the correlation self-energy and another modification that makes the Coulomb matrix sparse, analytic expansions of the interaction potentials around the point of divergence at k=0, and a nested density and density-matrix convergence scheme for hybrid-functional calculations. We show CPU timings for prototype semiconductors and illustrative results for GdN and ZnO.

Photoluminescence lineshape features of carbon δ-doped GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

The electronic structure and optical response of rutile, anatase and brookite TiO2 - Landmann, M; Rauls, E; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Spin resolved photoelectron spectroscopy of [Mn6IIICrIII]3 +single-molecule magnets and of manganese compounds as reference layers - Helmstedt, Andreas; Müller, Norbert; Gryzia, Aaron; Dohmeier, Niklas; Brechling, Armin; Sacher, Marc; Heinzmann, Ulrich; Hoeke, Veronika; Krickemeyer, Erich; Glaser, Thorsten; Bouvron, Samuel; Fonin, Mikhail; et al. (Journal of Physics: Condensed Matter)
Keywords: Condensed Matter Physics; General Materials Science

Glutamic acid adsorbed on Ag(110): direct and indirect molecular interactions - Blankenburg, S; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

QUANTUM ESPRESSO: a modular and open-source software project for quantum simulations of materials - Giannozzi, Paolo; Baroni, Stefano; Bonini, Nicola; Calandra, Matteo; Car, Roberto; Cavazzoni, Carlo; Ceresoli, Davide; Chiarotti, Guido L; Cococcioni, Matteo; Dabo, Ismaila; Dal Corso, Andrea; de Gironcoli, Stefano; et al. (Journal of Physics: Condensed Matter)

Coherent optoelectronics with single quantum dots - Zrenner, Artur; Ester, P; Michaelis de Vasconcellos, S; Hübner, M C; Lackmann, L; Stufler, S; Bichler, M (Journal of Physics: Condensed Matter)
The optical properties of semiconductor quantum dots are in many respects similar to those of atoms. Since quantum dots can be defined by state-of-the-art semiconductor technologies, they exhibit long-term stability and allow for well-controlled and efficient interactions with both optical and electrical fields. Resonant ps excitation of single quantum dot photodiodes leads to new classes of coherent optoelectronic functions and devices, which exhibit precise state preparation, phase-sensitive optical manipulations and the control of quantum states by electrical fields.

Theoretical and experimental investigations of Coulomb blockade in coupled quantum dot systems - Kaiser, F J; Kohler, S; Hänggi, P; Malecha, M; Ebbecke, J; Wixforth, A; Schumacher, H W; Kästner, B; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

Theoretical study of the localization of excess electrons at the surface of ice - Hermann, A; Schwerdtfeger, P; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Charge and spin dynamics in a two-dimensional electron gas - Pugžlys, A; Rizo, P J; Ivanin, K; Slachter, A; Reuter, Dirk; Wieck, A D; Wal, C H van der; Loosdrecht, P H M van (Journal of Physics: Condensed Matter)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Femtosecond time-resolved five-wave mixing at silicon surfaces - Meier, Torsten; Reichelt, Matthias; Koch, S W; Höfer, U (Journal of Physics: Condensed Matter)
The ultrafast dynamics of photoexcitations at silicon surfaces is investigated using a surface-sensitive purely optical technique. In the experiments, the diffracted second harmonic generated by sequences of ultrashort laser pulses is detected as a function of the time delay between the pulses. It is demonstrated that this five-wave-mixing technique can be used to measure the temporal evolution of the optical polarization and the photoexcited populations at the surface. The experimental results can be reproduced by numerical solutions of optical Bloch equations. The theoretical analysis allows one to investigate which dephasing times and relaxation processes are compatible with experiment. Furthermore, it is outlined how one can describe optical nonlinearities at surfaces using a microscopic theory within the framework of semiconductor Bloch equations.

Femtosecond time-resolved five-wave mixing at silicon surfaces - Meier, Torsten; Reichelt, Matthias; Koch, S W; Höfer, U (Journal of Physics: Condensed Matter)
The ultrafast dynamics of photoexcitations at silicon surfaces is investigated using a surface-sensitive purely optical technique. In the experiments, the diffracted second harmonic generated by sequences of ultrashort laser pulses is detected as a function of the time delay between the pulses. It is demonstrated that this five-wave-mixing technique can be used to measure the temporal evolution of the optical polarization and the photoexcited populations at the surface. The experimental results can be reproduced by numerical solutions of optical Bloch equations. The theoretical analysis allows one to investigate which dephasing times and relaxation processes are compatible with experiment. Furthermore, it is outlined how one can describe optical nonlinearities at surfaces using a microscopic theory within the framework of semiconductor Bloch equations.

Oxidation- and organic-molecule-induced changes of the Si surface optical anisotropy:ab initiopredictions - Schmidt, Wolf Gero; Fuchs, F; Hermann, A; Seino, K; Bechstedt, F; Paßmann, R; Wahl, M; Gensch, M; Hinrichs, K; Esser, N; Wang, S; Lu, W; et al. (Journal of Physics: Condensed Matter)

The Bethe–Salpeter equation: a first-principles approach for calculating surface optical spectra - Palummo, M; Pulci, O; Sole, R Del; Marini, A; Hahn, P; Schmidt, Wolf Gero; Bechstedt, F (Journal of Physics: Condensed Matter)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)

Assessment of the GW approximation using Hubbard chains - Pollehn, Thomas Joachim; Schindlmayr, Arno; Godby, Rex William (Journal of Physics: Condensed Matter)
We investigate the performance of the GW approximation by comparison to exact results for small model systems. The role of the chemical potentials in Dyson's equation as well as the consequences of numerical resonance broadening are examined, and we show how a proper treatment can improve computational implementations of many-body perturbation theory in general. Exchange-only and GW calculations are performed over a wide range of fractional band fillings and correlation strengths. We thus identify the physical situations where these schemes are applicable.

The anisotropic electron - positron momentum distribution in diamond - Nilen, R W N; Connell, S H; Britton, D T; Fischer, C G; Sendezera, E J; Schaaff, P; Schmidt, Wolf Gero; Sellschop, J P F; Verwoerd, W S (Journal of Physics: Condensed Matter)

Chemisorption of aluminium on GaAs(110) - Schmidt, Wolf Gero; Srivastava, G P (Journal of Physics: Condensed Matter)